Aneurysmal Subarachnoid Hemorrhage: Is the Time Until Intervention Related to Minor Disabilities in 6 Months? - Tebelskis, Yuri; Rabelo, Nícollas Nunes; Pipek, Leonardo Zumerkorn; Telles, João Paulo Mota; Barbosa, Guilherme Bitencourt; Barbat, Natalia Camargo; Coelho, Antônio Carlos Samaia da Silva; Yoshikawa, Marcia Harumy; Teixeira, Manoel Jacobsen; Figueiredo, Eberval Gadelha (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2023)
Background Aneurysmal subarachnoid hemorrhages (aSAHs) account for 5% of all strokes, an appalling number when it comes to the second most common cause of death worldwide. The basis of the treatment is clinical support and either endovascular or surgical intervention. The purpose of the present study is to analyze if the time from the onset of the thunderclap headache until treatment intervention is related to the degree of disability after 6 months.Methods In the present prospective observational study, data were collected from all patients (n = 223) admitted to the hospital with a diagnosis of aSAH. Patients whose data were missing or who missed the follow-up after 6 months were excluded. Then, the number of days from the thunderclap headache until the surgical intervention (Delta T) was obtained. The degree of disability was evaluated using standardized scales, Rankin Scale (RS) and Glasgow Outcome Scale (GOS), at the time of discharge as well as 6 months later. Then, the RS and GOS were correlated with Delta T.Results An average of 6.8 days was found from the onset of symptoms to the intervention, the average age was 54 years old, 73% were women and 55% were smokers. The mean Glasgow Coma Scale on admission was 13. The mean score on the Hunt and Hess scale was 2.1. From the radiological point of view, the mean size of the aneurysm was 6 mm, and the modified Fisher Scale was 3.1. Of the total number of patients at the end of the study (n = 78), 50 underwent microsurgical treatment (63%). Rankin scale at discharge was 1.9 and GOS was 4.5, with no statistically significant change at 6 months. Analyzing the data distribution using linear regression, no statistically significant correlation was found between the time until treatment and disability using RS and GOS (p > 0.05). The same results were found even analyzing age subgroups (≤ 45 years old, 45 to 55 years old, 55 to 70 years old, and > 70 years old with a p-value > 0.05).Conclusions The present study suggests that there is no linear correlation between Delta T and disability at 6 months for the population studied. However, more studies are needed to assess whether these findings may be present in other populations, especially with a shorter time from symptoms to intervention, since the greatest risk of rebleeding occurs in the first 3 days after the event.
Keywords: aneurysmal subarachnoid hemorrhage; disability; treatment; outcomes